Comparing the potential production and value of high‐energy liquid fuels and protein from marine and freshwater macroalgae. Issue 4 (19th June 2014) - Neveux, Nicolas; Magnusson, Marie; Maschmeyer, Thomas; de Nys, Rocky; Paul, Nicholas A.
Abstract The biomass production and biochemical properties of marine and freshwater species of green macroalgae (multicellular algae), cultivated in outdoor conditions, were evaluated to assess the potential conversion into high‐energy liquid biofuels, specifically biocrude and biodiesel and the value of these products. Biomass productivities were typically two times higher for marine macroalgae (8.5–11.9 g m−2 d−1, dry weight) than for freshwater macroalgae (3.4–5.1 g m−2 d−1, dry weight). The biochemical compositions of the species were also distinct, with higher ash content (25.5–36.6%) in marine macroalgae and higher calorific value (15.8–16.4 MJ kg−1) in freshwater macroalgae. Lipid content was highest for freshwater Oedogonium and marine Derbesia. Lipids are a critical organic component for biocrude production by hydrothermal liquefaction (HTL) and the theoretical biocrude yield was therefore highest for Oedogonium (17.7%, dry weight) and Derbesia (16.2%, dry weight). Theoretical biocrude yields were also higher than biodiesel yields for all species due to the conversion of the whole organic component of biomass, including the predominant carbohydrate fraction. However, all marine species had higher biomass productivities and therefore had higher projected biocrude productivities than freshwater species, up to 7.1 t of biocrude ha−1 yr−1 for Derbesia. The projected value of the six macroalgae was increased by 45–77% (up to US$7700 ha−1 yr−1) through the extraction of protein prior to the conversion of the residual biomass to biocrude. This study highlights the importance of optimizing biomass productivities for high‐energy fuels and targeting additional coproducts to increase value.